Investigation of high order stochastic differential equations using averaging method - Anh, Nguyen Dong; Hue, Ngo Thi Hong (Vietnam Journal of Mechanics, 2007)
The averaging method is a useful tool for investigating both deterministic and stochastic quasilinear system. In the stochastic problems, however, the method has often been developed only for mechanical systems subjected to white noise excitations.In the paper this method is applied to high order stochastic differential equations. The nonlinear oscillations in high order deterministic differential equations were investigated in the fundamental work of Prof. Nguyen Van Dao. As an application of high order stochastic differential equations the nonlinear oscillation of single degree of freedom systems subjected to the excitation of a class of colored noises is outlined. The results obtained show that the higher order averaging method can also be successfully extended to the cases of colored noise excitation.